assi_soln

# assi_soln - 1 Solutions of Assignment#1 STAT 330 Due in...

This preview shows pages 1–5. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 1 Solutions of Assignment #1 - STAT 330 Due in class: Thursday May 19 Important Note: You need to print out this page as the cover page for your assignment. LAST NAME: FIRST NAME: ID. NO.: QUESTION 1. /12 QUESTION 2. /8 QUESTION 3. /3 QUESTION 4. /2 QUESTION 5. /9 QUESTION 6. /6 TOTAL: /40 2 1. Solution: (a) (i) ∞ X x =0 f ( x ) = 1 ⇒ ∞ X x =0 k (0 . 3) x = k · 1 1- . 3 = 1 ∴ k = 0 . 7 (ii) F ( x ) = P ( X ≤ x ) = X r ≤ x f ( r ) = x X r =0 . 7(0 . 3) r = 0 . 7 · 1- . 3 x +1 1- . 3 = 1- . 3 x +1 , x = 0 , 1 , 2 ,... which gives a step function: F ( x ) = 1- . 3 n +1 , n ≤ x < n + 1 , otherwise where n = 0 , 1 , 2 ,... (iii) E ( X ) = ∞ X x =0 xf ( x ) = ∞ X x =0 x · . 7 · (0 . 3) x = ∞ X x =1 . 21 · x (0 . 3) x- 1 = 0 . 21 ∞ X x =1 x (0 . 3) x- 1 = 0 . 21( 1 1- . 3 ) 2 = 3 7 where we used the technique: ∞ X n =1 ny n- 1 = ∞ X n =1 ( y n ) = ( ∞ X n =1 y n ) = ( y 1- y ) = 1 (1- y ) 2 , for | y | < 1 3 (b) (i) Z ∞ kx 2 e- λx dx = 1 , let y = λx, then Z ∞ k ( y λ ) 2 e- y 1 λ dy = k λ 3 Z ∞ y 3- 1 e- y dy = k λ 3 Γ(3) = 2 k λ 3 ⇒ k = λ 3 2 (ii) When x > 0: F ( x ) = Z x f ( t ) dt = Z x λ 3 2 t 2 e- λt dt = Z λx 1 2 y 2 e- y dy, let y = λt = Z λx 1 2 y 2 d (- e- y ) =- 1 2 y 2 e- y λx + Z λx e- y · ydy =- 1 2 ( λx ) 2 e- λx + y (- e- y ) λx + Z λx e- y dy = 1- e- λx 1 + λx + 1 2 ( λx ) 2 When x ≤ 0: F ( x ) = 0, therefore, F ( x ) = 1- e- λx (1 + λx + 1 2 ( λx ) 2 ) , x > , x ≤ 4 (iii) E ( X ) = Z ∞-∞ xf ( x ) dx = Z ∞ x · λ 3 2 x 2 e- λx dx = λ 3 2 Z ∞ x 3 e- λx dx = 1 2 λ Z ∞ y 4- 1 e- y dy, let y = λx = 1 2 λ Γ(4) = 3! 2 λ = 3 λ (c) (i) Z ∞ k (1 + x )- ( θ +1) dx = 1 ∴- k θ (1 + x )- θ ∞ = 1 k θ = 1 ⇒ k = θ (ii) when x > 0: F ( x ) = Z x θ (1 + t )- ( θ +1) dt = θ [- (1 + t )- θ θ | x ] = 1- (1 + x )- θ when x ≤ 0: F ( x ) = 0 Therefore, F ( x ) = 1- (1 + x )- θ , x > , x ≤ (iii) E ( X ) = Z ∞ x · θ (1 + x )- ( θ +1) dx = Z ∞ 1 ( y- 1) θy- ( θ +1) dy, let y = 1 + x = Z ∞ 1 θy- θ dy- Z ∞ 1 θy- ( θ +1) dy = θ · 1- θ + 1 y- θ +1 ∞ 1- θ ·...
View Full Document

## This note was uploaded on 07/13/2011 for the course STAT 330 taught by Professor Paulasmith during the Spring '08 term at Waterloo.

### Page1 / 15

assi_soln - 1 Solutions of Assignment#1 STAT 330 Due in...

This preview shows document pages 1 - 5. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online